Hypofractionated radiotherapy alone with 2.4 Gy per fraction for head and neck cancer during the COVID‐19 pandemic: The Princess Margaret experience and proposal. Issue 15 (1st June 2020) - Huang, Shao Hui; O'Sullivan, Brian; Su, Jie; Ringash, Jolie; Bratman, Scott V.; Kim, John; Hosni, Ali; Bayley, Andrew; Cho, John; Giuliani, Meredith; Hope, Andrew; Spreafico, Anna; et al.
Abstract : Background: The objective of this study was to identify a subgroup of patients with head and neck squamous cell carcinoma (HNSCC) who might be suitable for hypofractionated radiotherapy (RT‐hypo) during the COVID‐19 pandemic. Methods: HNSCC cases (oropharynx/larynx/hypopharynx) treated with definitive RT‐hypo (60 Gy in 25 fractions over 5 weeks), moderately accelerated radiotherapy (RT‐acc) alone (70 Gy in 35 fractions over 6 weeks), or concurrent chemoradiotherapy (CCRT) during 2005‐2017 were included. Locoregional control (LRC) and distant control (DC) after RT‐hypo, RT‐acc, and CCRT were compared for various subgroups. Results: The study identified 994 human papillomavirus–positive (HPV+) oropharyngeal squamous cell carcinoma cases (with 61, 254, and 679 receiving RT‐hypo, RT‐acc, and CCRT, respectively) and 1045 HPV– HNSCC cases (with 263, 451, and 331 receiving RT‐hypo, RT‐acc, and CCRT, respectively). The CCRT cohort had higher T/N categories, whereas the radiotherapy‐alone patients were older. The median follow‐up was 4.6 years. RT‐hypo, RT‐acc, and CCRT produced comparable 3‐year LRC and DC for HPV+ T1‐2N0‐N2a disease (seventh edition of the TNM system [TNM‐7]; LRC, 94%, 100%, and 94%; P  = .769; DC, 94%, 100%, and 94%; P  = .272), T1‐T2N2b disease (LRC, 90%, 94%, and 97%; P  = .445; DC, 100%, 96%, and 95%; P  = .697), and T1‐2N2c/T3N0‐N2c disease (LRC, 89%, 93%, and 95%; P  = .494; DC, 89%, 90%, and 87%; P  = .838). Although LRC was also similar for T4/N3 disease (78%, 84%, and 88%; P  = .677), DC was significantly lower with RT‐hypo or RT‐acc versus CCRT (67%, 65%, and 87%; P  = .005). For HPV– HNSCC, 3‐year LRC and DC were similar with RT‐hypo, RT‐acc, and CCRT in stages I and II (LRC, 85%, 89%, and 100%; P  = .320; DC, 99%, 98%, and 100%; P  = .446); however, RT‐hypo and RT‐acc had significantly lower LRC in stage III (76%, 69%, and 91%; P  = .006), whereas DC rates were similar (92%, 85%, and 90%; P  = .410). Lower LRC in stage III predominated in patients with laryngeal squamous cell carcinoma receiving RT‐acc (62%) but not RT‐hypo (80%) or CCRT (92%; RT‐hypo vs CCRT: P  = .270; RT‐acc vs CCRT: P = .004). CCRT had numerically higher LRC in comparison with RT‐hypo or RT‐acc in stage IV (73%, 65%, and 66%; P  = .336). Conclusions: It is proposed that RT‐hypo be considered in place of CCRT for HPV+ T1‐T3N0‐N2c (TNM‐7) HNSCCs, HPV– T1‐T2N0 HNSCCs, and select stage III HNSCCs during the COVID‐19 outbreak. Abstract : Hypo‐fractionated radiotherapy has disease control comparable to that of chemoradiotherapy in select head and neck cancers, and it is a potential alternative for this subgroup during the COVID‐19 pandemic.